2023
DOI: 10.1111/jcal.12776
|View full text |Cite
|
Sign up to set email alerts
|

Improving mathematics assessment readability: Do large language models help?

Abstract: Background: Readability metrics provide us with an objective and efficient way to assess the quality of educational texts. We can use the readability measures for finding assessment items that are difficult to read for a given grade level. Hard-to-read math word problems can put some students at a disadvantage if they are behind in their literacy learning. Despite their math abilities, these students can perform poorly on difficult-to-read word problems because of their poor reading skills. Less readable math … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results of RQ1 showed that the GPT models were able to generate more readable feedback with greater consistency than human instructors. This is not surprising because the ability of LLMs to provide readable responses in various contexts has been demonstrated in the literature Li and Xing (2021); Patel et al (2023). For example, Li and Xing (2021) indicated that GPT-2 could provide readable and coherent replies to human learners' posts on MOOC discussion forums to a similar extent compared to human instructors.…”
Section: Interpretation Of the Resultsmentioning
confidence: 82%
“…The results of RQ1 showed that the GPT models were able to generate more readable feedback with greater consistency than human instructors. This is not surprising because the ability of LLMs to provide readable responses in various contexts has been demonstrated in the literature Li and Xing (2021); Patel et al (2023). For example, Li and Xing (2021) indicated that GPT-2 could provide readable and coherent replies to human learners' posts on MOOC discussion forums to a similar extent compared to human instructors.…”
Section: Interpretation Of the Resultsmentioning
confidence: 82%
“…Patel et al (2023) contributed a paper that was directly aimed at teachers, too. Focusing on the output and action level, they used the generative large language model GPT‐3 to reduce the linguistic difficulty of mathematical word problems.…”
Section: Paper Contributionsmentioning
confidence: 99%
“…In the era of LLMs, language model recommender systems have been proposed to increase transparency and control for students by enabling them to interact with the learning system using natural language [110]. LLMs can interpret natural language user profiles and use them to modulate learning materials for each session [111]. For example, Zhang et al [112] proposed a language model recommender system leveraging several language models, including GPT2 and BERT.…”
Section: Using Language Models To Increase Personalizationmentioning
confidence: 99%